The impact of COVID-19 and its policy responses on local economy and health conditions - Ali Gungoraydinoglu; Ilke Öztekin; Özde Öztekin (Journal of Risk and Financial Management, 2021)
US states have implemented lockdown measures to contain the COVID-19 pandemic. We assess the impact of state policy responses on local economic and health conditions, with the goal to shed light on marginal health benefits and economic costs associated with social distancing. We find that lockdown measures are effective in alleviating disease severity, but yield significant contraction of the economy. Deteriorating health conditions are disruptive to the labor supply, financial health, and economic output. The adverse economic impact of lockdowns exceeds the economic damage brought by the disease itself, but health conditions better forecast economic contraction outcomes.
Keywords: I15; I18; I30; J20; 330; bankruptcy; COVID-19; economic growth; lockdown; pandemic; unemployment